Association of Carotid Artery Intima Media Thickness With Ischemic Stroke Patients - Uddin, Md Jasim; Rahman, Aminur; Islam, Md Rafiqul; Sabuj, Md Shahidullah; Mamun, Abdullah Al; Roy, Niloy Ranjan (Bangladesh Journal of Medicine, 2022)
Background: Atherosclerotic risk factors frequently lead to ischemic stroke. The thickness of the carotid intima-media thickness (CIMT) is a significant indicator for early atherosclerosis alterations. The aim of the study is to evaluate the association between ischemic stroke patients and CIMT. Methods: A total of 50 patients were recruited in this cross-sectional descriptive study which was carried out in the Department of Neurology, BSMMU, from January 2015 to June 2016. All patients of ischemic stroke were confirmed by history, examination and CT scan of head/MRI of brain. Carotid ultrasound scan was done to detect intima-media thickness (IMT) of both sided carotid bifurcation, common carotid and internal carotid artery and performed by a single sonographer at the Department of Neurology, BSMMU. Results: This population has a total of 27 male and 23 female with mean age 60.7± 13.6 years. Maximum patients (72%) were found to be above 50 year of age. After risk factor stratification among the study population, HTN, dyslipidemia was the most followed by positive family history, smoker, DM, IHD. Among study population 45 cases were anterior circulation stroke and only 5 cases were posterior circulation stroke. Maximum mean IMT=1.2± 0.3, minimum mean IMT=1.0±0.10 mm and least IMT was 0.7mm. (Normal CIMT value is < 0.8mm). The mean IMT was higher at symptomatic side in comparison to the asymptomatic side. Higher IMT was found mostly at the carotid bifurcation and higher IMT at one site was significantly correlated with other sites (r= +0.435, p=0.002), there was also correlation between IMT and risk factor (r=+0.265, p=0.063). Increased IMT was more marked in patients with risk factors in comparison to without risk factor, like smoker & nonsmoker but not statistically significant (ORR=2.00, 95% CI 0.636- 6.286, p=0.233). Conclusion: The present Study found that extra-cranial carotid artery intima media thickness (IMT) was higher than normal level in ischemic stroke patients. Higher CIMT was found at symptomatic side in comparison to the asymptomatic side. Bangladesh J Medicine 2022; 33: 24-30